2021
DOI: 10.1080/07391102.2021.1911854
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, α-glucosidase and α-amylase inhibitory activities, acute toxicity and molecular docking studies of thiazolidine-2,4-diones derivatives

Abstract: Synthesis, biological evaluation, acute toxicity and molecular docking studies of thiazolidine-2,4-diones derivatives as new class of α-glucosidase and α-amylase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Alpha-glucosidase contains catalytic residues such as ASN-258, ASP-327, ILE-143, and ASP-382 [ 23 ]. Similarly, apigenin-7- O -glucoside formed several hydrogen bonds with the active site residues ASP-60, ASN-258, ASP-327, ILE-143, and ASP-382, where all residues except ASP-60 and ASN-258 generated a double hydrogen bond with the alpha-glucosidase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpha-glucosidase contains catalytic residues such as ASN-258, ASP-327, ILE-143, and ASP-382 [ 23 ]. Similarly, apigenin-7- O -glucoside formed several hydrogen bonds with the active site residues ASP-60, ASN-258, ASP-327, ILE-143, and ASP-382, where all residues except ASP-60 and ASN-258 generated a double hydrogen bond with the alpha-glucosidase.…”
Section: Discussionmentioning
confidence: 99%
“…This research study was designed to reveal the specific interaction between two or more molecules (molecular recognition) and the binding mechanism of betel compound to alpha-amylase and alpha-glucosidase by utilizing molecular modelling and molecular dynamics simulation studies [ 13 ]. The alpha-amylase enzyme contains catalytic residues such as ASP-197, GLU-233, & ASP-300 which act on both α-D-(1,4) linkages and α-D-(1,6) linkages of large oligosaccharide molecules and break them into disaccharides and trisaccharides [ 8 ].These disaccharides and trisaccharides further break down into monomer molecules with the help of alpha-glucosidase which contains ASN-258, 327, 382 and ILE-143 catalytic residues [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other heterocyclic systems featuring a thiazolidine scaffold, our compound 8d exhibits a very satisfying inhibition potency. Examples are thiazolidine-2,4-dione derivatives (IC 50 values in the range 18.19 to 208.10 μM in comparison with Acarbose 2.97 μM) and 2-(( Z )-5-(arylidene)-4-oxo-2-thioxothiazolidin-3-yl) acetic acid derivatives with IC 50 = 170.40– 384.45 μM as compared to Acarbose (IC 50 = 29.71 μM) …”
Section: Biological Activitiesmentioning
confidence: 99%
“…Examples are thiazolidine-2,4dione derivatives (IC 50 values in the range 18.19 to 208.10 μM in comparison with Acarbose 2.97 μM) 44 tives with IC 50 = 170.40− 384.45 μM as compared to Acarbose (IC 50 = 29.71 μM). 45 In Vivo Antidiabetic Activity in Diabetic Rats. To further evaluate the potential of the most potent 2-aminothiazol-4(5H)-one derivative 8d in controlling hyperglycemia and to confirm its in vitro α-amylase inhibitory activity, in vivo experiments were conducted with alloxan-induced diabetic rats.…”
Section: ■ Biological Activitiesmentioning
confidence: 99%
“…Fettach et al synthesized series of 5-arylidenethiazolidine-2,4-diones (84a-84e) and their 3-allyl analogues (85a-85e) (Figure 35). The synthesized compounds were evaluated for their inhibitory activity towards α-amylase and α-glucosidase enzymes in vitro [87]. It has been shown that all tested derivatives had good or moderate activity toward αglucosidase (IC 50 = 43.85-380.10 µM) in comparison with standard inhibitor (acarbose IC 50 = 97.12 µM).…”
Section: Antidiabetic Activitymentioning
confidence: 99%